2021
DOI: 10.1002/icd.2265
|View full text |Cite
|
Sign up to set email alerts
|

Shyness and social–emotional development among Chinese children: A systematic review and meta‐analysis

Abstract: Shyness, which is characterized by social withdrawal behaviours and approaching-withdrawal conflicted social motivations, is suggested to influence children's socialemotional development. This study examined the association between shyness and social-emotional development among Chinese children aged 3 to 12. A systematic search of both Chinese and international databases for relevant research between 1990 and 2020 yielded 23 studies (n = 9,009 children), which were systematically reviewed. Among them, 15 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 93 publications
2
21
0
Order By: Relevance
“…This finding is in line with the meta-analysis (X. Zhang et al, 2021) and some recent Chinese studies (Chen et al, 2014;Zhai et al, 2020). Moreover, fear and shyness were moderately interrelated.…”
Section: Summary Of Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is in line with the meta-analysis (X. Zhang et al, 2021) and some recent Chinese studies (Chen et al, 2014;Zhai et al, 2020). Moreover, fear and shyness were moderately interrelated.…”
Section: Summary Of Findingssupporting
confidence: 89%
“…According to the pooled association (r = −.22) found in the meta-analysis by X. Zhang et al (2021), at least 127 and 160 participants are needed to obtain the power of .80 at the significance levels of .10 and .05, respectively. Considering the complexity of the research designs and our focus on potential changes in associations across historical time, we first report the findings from the most recent birth cohort (2016-2019), followed by the findings from the older (2014)(2015) and oldest birth cohorts of children (2009)(2010).…”
mentioning
confidence: 99%
“…This was a multidimensional construct. By comprehensively integrating the measurements of SED utilized in Chinese child group (Li et al, 2010; Wang et al, 2019; Zhang et al, 2021), we selected five different dimensions, including self‐esteem, social competence, emotional competence, resilience and pro‐social behaviour to measure SED in this study.…”
Section: Methodsmentioning
confidence: 99%
“…In Eastern countries like China, young children's social inhibition can sometimes be considered as age‐normative and even favorably because it is non‐disruptive and involves fewer emotional problems (cf. X. Chen et al., 2021; Zhang et al., 2021). As such, it is likely that in the early school years, social inhibition still has a more positive influence on teacher‐child relationships in Eastern countries than in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on 3‐to‐6‐year‐old children, however, revealed mixed results. Social inhibition was sometimes associated with more peer exclusion and other times was not associated significantly with peer preference at all (see Zhang et al., 2021 for a review). These mixed findings suggest that social inhibition may be less harmful to young children's peer relationships than those of older children, probably because social inhibition is still considered age‐normative for young children in China (Zhang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%